Collaborative writing and discussion in vocational education: Effects on learning and self-efficacy beliefs - Ortoleva, Giulia; Bétrancourt, Mireille (Journal of Writing Research, 2015)
Most professional education tracks combine school learning with practical workplace training. Although in theory alternating between these two settings is a great opportunity for learning, vocational education students encounter difficulties in integrating the formal explicit knowledge imparted in school with the informal tacit knowledge acquired in the workplace. This design study explores the potential of writing and peer collaboration as mediating tools to facilitate the articulation of conceptual and experiential knowledge. In the context of a school for social and health care assistants, 40 first- and second-year students wrote about critical situations encountered in the workplace, shared them with their classmates, and engaged in written and oral discussions with colleagues and the teacher. A web-based collaborative writing tool (wiki) was used for writing and facilitating participants’ interactions. The results showed significant gains in self-efficacy beliefs and performance on a case-based competence test for the first-year students, but not for those in the second-year. In addition, all students reported a high level of satisfaction with the instructional scenario and particularly its collaborative dimension. The discussion raises some issues and recommendations regarding the design of learning activities involving writing and peer feedback to support students in articulating conceptual and experiential knowledge